Un’introduzione critica alla condizione intersex (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The article aims at providing some insights into the emerging topic of “intersex”. In doing it, the paper describes and analyses some issues currently under academic and public debate, such as the correct definition of intersex and its quantification, the hurdles in terms of marital status, as well as the legitimacy of the neonatal surgeries.
Keywords: Intersex; Dsd; Intersexuality; Genital surgeries; Genital mutilation